Travel Patterns for Nature Tourism at Lake Aek Natonang Samosir Regency - Lestari Situmeang; Ria Natalia Tamba; Yunester Anastasya Nainggolan (Politeknik Sahid, 2026)
This study identifies the attraction of Lake Aek Natonang tourist attractions and creates a Travel Pattern to make it easier for tourists to go to Lake Aek Natonang. The data collection techniques in this study were through observation, interviews, and documentation studies, then analyzed using a descriptive qualitative method to understand the characteristics and patterns of Lake Aek Natonang tourist trips. The results of the study show that the tourist attraction of Lake Aek Natonang is in the form of natural beauty that is still preserved, supporting facilities, and tourist activities such as fishing, hiking, and camping. In addition, the recommended travel pattern is the Destination Region Loop, where the movement of tourists begins with a route around other destinations. After completing the tour in a circular (circular pattern), tourists return to their place of origin via the shortest route between the main destination and the place of departure origin. This pattern makes it easier for tourists to enjoy various interesting destinations around the lake while optimizing the tourist experience through efficient and attractive routes. These findings provide valuable insights for local governments and tourism managers to develop strategic, well-integrated tour packages that boost regional tourism competitiveness.